2003
DOI: 10.1021/es030327a
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Perfluorocarbons

Abstract: Collectively, man-made emissions of a few greenhouse gases may cause about the same amount of global warming as increasing carbon dioxide. Among the most potent of these non-CO2 greenhouse gases are the perfluorocarbons that have extraordinarily long atmospheric lifetimes of 10,000 to more than 50,000 yr. We report atmospheric concentrations over two decades, between 1978 and 1997, of the three most abundant perfluorocarbons--CF4, C2F6, and C3F8--and delineate the sources that account for the present abundance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
52
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 12 publications
6
52
0
Order By: Relevance
“…Anthropogenic were historically emitted as by-products of aluminum production and are now also emitted from the electronics industry. However, the onset and extent of PFC emissions from the electronics industry is poorly known due to limited reporting (Khalil et al 2003;Worton et al 2007;EDGAR 2009;Mühle et al 2010).…”
Section: (C) Carbon Monoxidementioning
confidence: 99%
“…Anthropogenic were historically emitted as by-products of aluminum production and are now also emitted from the electronics industry. However, the onset and extent of PFC emissions from the electronics industry is poorly known due to limited reporting (Khalil et al 2003;Worton et al 2007;EDGAR 2009;Mühle et al 2010).…”
Section: (C) Carbon Monoxidementioning
confidence: 99%
“…Part of this is of natural origin . The main source of CF 4 , however, is anthropogenic and related to aluminum refining and to semiconductor manufacturing . Recent studies from space and from the ground report a slowdown of the CF 4 mixing ratio increase during the 1990s, which supports recent aluminum industry reports of reduced CF 4 emissions.…”
Section: Introductionmentioning
confidence: 65%
“…Also, much of the C2F6 used in the semiconductor manufacturing was released to the atmosphere. By analyzing the stored air, Khalil et al (2003) found that the emission concentrations of CF4 and C2F6 increased about two and ten times, respectively over the past four decades (from 1960 to 2000). Khalil et al also found that the increasing trend of CF4 emissions has slowed in recent years, but the reduction in the emission rate in the aluminum industry is partially offset by the increasing use of CF4 in the semiconductor industry.…”
Section: Introductionmentioning
confidence: 99%